The Contribution of Group Guidance Services to Increasing the Study Concentration of Class X Students at SMA Negeri 3 Samarinda 2020/2021 - Afy Defisah; Masnurimma Heriansyah; Andi Wahyu Irawan; Dydik Kurniawan; Yasintha Sari Pratiwi (Faculty of Teacher Training and Education, Mulawarman University, 2021)
This study aims to determine whether there is a contribution of group guidance services to increasing the learning concentration of class X students at SMA Negeri 3 Samarinda 2020/2021. This type of research is ex post facto quantitative with a correlational design. 138 samples from a population of 353 students, samples were taken using a purposive sampling technique with the consideration that students have low learning outcomes and who have difficulty in concentrating when viewed from the results of the AKPD analysis. Data collection techniques using questionnaires and interviews. The prerequisite test using SPSS 25.0 For Windows is the normality test using the Kolmogorov-Smirnov formula and the linearity test by looking at the sig value. deviation from linearity. The data analysis technique uses a simple linear regression test to see whether there is a contribution from group guidance services to increasing student learning concentration and is proven by looking at the results of the F test whether the hypothesis is accepted or rejected. The results of the study were 35,400 2.28 or Fcount Ftable which means Ha is accepted and H0 is rejected, meaning that there is a contribution from group guidance services to increasing the learning concentration of class X students. And the contribution is 21% based on the coefficient of determination (Rsquare). So that group guidance services can be used as a strategy in an effort to increase the learning concentration of class X students.